2015
DOI: 10.1016/j.jped.2014.09.009
|View full text |Cite
|
Sign up to set email alerts
|

Socio-economic and demographic determinants of childhood anemia

Abstract: The results suggest a need for proper planning and implementation of preventive measures to combat child anemia. Economically under-privileged groups, maternal nutrition and education, and birth control measures should be priorities in the programs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
25
5
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(46 citation statements)
references
References 16 publications
10
25
5
2
Order By: Relevance
“…Risk of anemia increased with increasing maternal educational level. This is in contrast to an Indian study were low educational level and anemia among the mother significantly increases the risk of childhood anemia [37]. Our results are also in contrast to another study by de Vienne et al who found an association between young age and risk of maternal anemia [13], which is known to increase the risk of anemia in the child.…”
Section: Discussioncontrasting
confidence: 99%
“…Risk of anemia increased with increasing maternal educational level. This is in contrast to an Indian study were low educational level and anemia among the mother significantly increases the risk of childhood anemia [37]. Our results are also in contrast to another study by de Vienne et al who found an association between young age and risk of maternal anemia [13], which is known to increase the risk of anemia in the child.…”
Section: Discussioncontrasting
confidence: 99%
“…Here religious affiliation has impact on severity levels of child anemia status. This result was supported by other related studies conducted in North-East India [30] and India [31].…”
Section: Discussionsupporting
confidence: 88%
“…According to National Family Health survey (NFHS-3), anemia is common in India among the schedule caste and tribes and among the children with low socioeconomic status. 16 Current study shows that, acute painful crisis (59.01%) was the most common cause for hospitalization, followed by severe anemia (39.34%) and infections (36.06%). In a study by Akar NA.…”
Section: Resultsmentioning
confidence: 90%